Optimalt ekologiskt - Holm, Johanna (2008)
This is a graduate work at the Swedish University of Agricultural Sciences, The Department of Urban and Rural Development, Ultuna. The purpose of this paper has been to find out and describe principles for designing parks that offers good recreational and aesthetical values and require little amount of carbon dioxide emissions during their maintenance. The purpose has also been to see if it's possible to use city wastewater in some extent to assure the plants water supply and to find other means to make it less necessary to use purified water for watering.